Critical versus descriptive intersectionality: towards a political tool for the liberation of peoples - VISOTSKY , Jessica (Utopía y Praxis Latinoamericana, 2023)
In this work we focus on delving into the perspective of intersectionality as a decolonial category, a relevant category for the approach to human and peoples’ rights. We delve into the uses that are being made of it, raising the need to discern between a descriptive intersectionality and one critical interseccionality, and at that point we put this category in dialogue with that of territory.This article is the result of reflections within the framework of fieldwork with migrants in the cities, with indigenous women, with workers from recovered factories, with rural and mountain dwellers and accompaniment work with women, men and diversities in the face of the violation of human rights and of peoples.